Isolated Identities: The Storied Lives of LGB Emerging Adults on a Rural, Community College Campus - Erin J Ferris; Miriam S Phillips (Adult Education Research Conference, 2016)
Community colleges serve diverse populations including LGB emerging adults who are attempting to find their place within society. Through a thematic analysis of narrative interviews and a focus group we found on one, rural campus there is a culture of isolation, which may limit individuals growth both personally and academically.
Keywords: LGB; Identity; Isolation; Rural Community Colleges